CD44 knockdown alters miRNA expression and their target genes in colon cancer - Maltseva, Diana; Zhiyanov, Anton; Lange, Tobias; Tonevitsky, Alexander (Frontiers in Immunology, 2025)
IntroductionMetastasis formation poses a significant challenge to oncologists, as it severely limits the survival of colorectal cancer (CRC) patients. Recently, we demonstrated that CD44 promotes spontaneous distant metastasis in a CRC xenograft model. The depletion of CD44 was associated with reduction in hypoxia, EMT, as well as improved mitochondrial metabolism in primary tumor. Collectively, these effects decreased the metastatic potential of the CRC xenograft tumors under investigation. In this study we explore the molecular mechanisms by which CD44 knockdown (kd) leads to such substantial changes of tumor properties.MethodsUsing miRNA-Seq data combined with bioinformatic analysis, we investigated the role of miRNA expression changes in the metastasis prevention observed with CD44 kd.ResultsAmong the differentially expressed miRNAs, three members of Let-7 family (let-7a-5p, let-7b-5p, and let-7c-5p), two isoforms of miR-203a (canonical miR-203a-3p and its +1 5’-isoform), miR-101-3p, miR-200b-3p|+1 5’-isoform, miR-125a-5p, and miR-185-5p were identified as potentially involved in regulating CD44-mediated metastasis. Gene set analysis of differentially expressed mRNA targets of these miRNAs, along with an examination of key regulators driving the observed changes in both mRNA and miRNA expression profiles, suggests that the CD44-STAT3-Let-7 miRNA axis as one of the most relevant in regulation of colon cancer metastasis via the CD44 receptor.DiscussionOur findings suggest a regulatory relationship between CD44, Let-7 miRNAs, and STAT3 in HT-29 tumors. Additionally, we propose the potential involvement of both isoforms of miR-203a (canonical and its +1 5’-isoform) in this regulatory network and suggest a role for miR-101-3p and miR-125a-5p in metastasis regulation through CD44 kd.